2023
DOI: 10.3390/antiox12010120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Inactivation of Phosphatase PTEN and TCPTP in Fatty Liver Disease

Abstract: Alcoholic liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD) are becoming increasingly prevalent worldwide. Despite the different etiologies, their spectra and histological feature are similar, from simple steatosis to more advanced stages such as steatohepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. Studies including peroxiredoxin knockout models revealed that oxidative stress is crucial in these diseases, which present as consequences of redox imbalance. Protein tyrosine phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 132 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…Notably, JUN, TLR4, and ANXA5, like ANXA2, showed a trend of upregulation with increasing NAFLD in our three datasets. JUN, TLR4 ( 42 ), EGFR ( 43 ), and TNF ( 44 ) were confirmed to promote the progression of NAFLD in previous studies, while ANXA5 ( 45 ) and PTEN ( 46 ) were identified as protective factors. TP53 has a dual role in NAFLD ( 47 ).…”
Section: Discussionmentioning
confidence: 54%
“…Notably, JUN, TLR4, and ANXA5, like ANXA2, showed a trend of upregulation with increasing NAFLD in our three datasets. JUN, TLR4 ( 42 ), EGFR ( 43 ), and TNF ( 44 ) were confirmed to promote the progression of NAFLD in previous studies, while ANXA5 ( 45 ) and PTEN ( 46 ) were identified as protective factors. TP53 has a dual role in NAFLD ( 47 ).…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, the migration of HSCs is affected by EC-derived EVs containing sphingosine kinase 1 (SK1), which mediates HSC chemotaxis through the SK1-S1P pathway ( 49 ). Besides, Studies have reported that PTEN has been proved to play an important role in the fibrosis in kidney ( 106 ) and liver ( 107 ) and highly related to exosome. For example, lipotoxic hepatocytes exosome transplantation aggravated the degree of PTEN-induced expression of putative protein kinase 1 (PINK1) mediated mitophagy suppression, steatohepatitis, lipidosis, and fibrosis in the livers of NAFLD mice with cirrhosis ( 108 ).…”
Section: The Role Of Evs In Nafldmentioning
confidence: 99%
“…MC activation comes with ROS production; ROS regulate various signaling pathways, thus providing the release of inflammatory mediators and various cytokine production. Protein tyrosine phosphatases (PTPs) are a superfamily of enzymes that are the main targets for ROS due to an oxidation-susceptible nucleophilic cysteine at their active site [ 119 ]. As reported, direct and indirect regulations of class I and II Cys-based protein tyrosine phosphatases (PTEN, LMW-PTP, SHP-2, PTP-PEST, PTP1B, DEP-1, TC45, LAR, etc.)…”
Section: Reactive Oxygen Species In the Mechanisms Of Activation Of M...mentioning
confidence: 99%